2016
DOI: 10.22159/ajpcr.2017.v10i1.15067
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Short Sleep Duration and Obesity in Medical Students

Abstract: Objective: Adequate sleep has been considered important for the adolescent's health and well-being. On the other hand, self-imposed sleep curtailment is now recognized as a potentially important and novel risk factor for obesity. The objective of the study is to find the association between short sleep duration and obesity (by calculating the body mass index [BMI]) among medical students. Methods:The study was conducted on 100 medical students. A brief history of sleep duration was taken. The height and weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…[24] Few similar researches have been done in medical students, results of which are corroborative with the present one. [25,26] The college students are more vulnerable to sleep disorders, as they are facing great academic pressure, social pressure, new environment, erratic schedules, and lifestyle changes. Most of the studies examining sleep among them have focused on the relationship between sleep habits and academic performance and mental health problems with the recognition that they are experiencing sleep problems that negatively impact their health and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…[24] Few similar researches have been done in medical students, results of which are corroborative with the present one. [25,26] The college students are more vulnerable to sleep disorders, as they are facing great academic pressure, social pressure, new environment, erratic schedules, and lifestyle changes. Most of the studies examining sleep among them have focused on the relationship between sleep habits and academic performance and mental health problems with the recognition that they are experiencing sleep problems that negatively impact their health and well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike most cellulose originating from secondary‐wall fibers, the cellulose obtained from SBP is a typical primary‐wall cellulose . SBP has been traditionally employed as an excellent emulsifier, thickener or stabilizer, along with a number of potential non‐food industrial applications . Dufresne et al showed that SBP can produce films with good appearance and satisfactory mechanical properties; it appears to have good potential as a film forming agent.…”
Section: Introductionmentioning
confidence: 99%
“…This study shows that there is statically significant association between short sleep duration and overweight/obesity. Tapaswini Mishra et al 18 in their study showed an association between short sleep duration and obesity which was highly significant. Sanjay R. Patel et al 19 in a systematic review of crosssectional and cohort studies of children found that short sleep duration is strongly and consistently associated with concurrent and future obesity.…”
Section: Discussionmentioning
confidence: 91%